Apoio social e funcionalidade familiar de pessoas idosas em cuidados paliativos no contexto hospitalar: mapeamento das evidências e descrição do perfil - Silva, Ana Laura de Souza (Universidade Federal de São Carlos, 2024)
Population aging is a global reality that demands new approaches to the healthcare of older people. Among these, palliative care emerges as essential to improving the quality of life for patients with severe and life-threatening illnesses. In this context, social support and family functionality play crucial roles, which can influence the general state and well-being of these patients, as well as facilitate adaptation to debilitating conditions. Objective: To analyze the social support and family functionality of older people eligible for and/or receiving palliative care in the hospital context, mapping the existing scientific evidence and describing the sociodemographic and clinical profile of this population. Method: The study was developed in two stages: a scoping review and a pilot study. The scoping review mapped scientific evidence in the databases of the Virtual Health Library, Embase, Medline/PubMed, and Scopus between 2019 and 2024. The pilot study included ten hospitalized older people, eligible for palliative care, in which sociodemographic, clinical, social support, and family functionality data were collected. Results: In the scoping review, four studies were selected, with participants predominantly male, ages ranging from 66 to 91 years, and multiple chronic diseases. Feelings of depression, anxiety, loneliness, and pain were prevalent. The social support network was perceived positively, but family functionality showed weaknesses, generating insecurity. Perceived social support increased over time, while feelings of loneliness and depression decreased. In the pilot study, most older people were male, diagnosed with neoplasms, and dependent on activities of daily living. The highest perceived social support score was in the material dimension, while the lowest was in emotional support. Family functionality was considered good, with weak but harmonious family ties. Conclusion: The study revealed that social support and family functionality are important factors in the experience of patients in palliative care, especially regarding emotional support and social interaction during hospital care. However, caregiver burden and family conflicts can lead to family dysfunction and negatively impact older people in hospital-based palliative care.
Social support and family functionality of elderly people in palliative care in the hospital context: mapping evidence and describing the profile
Keywords: Idoso; Cuidados paliativos; Apoio social; Hospitalização; Relações Fa; Aged; Palliative care; Social support; Hospitalization; Family relations; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE